POROUS FLY ASH-BASED GEOPOLYMER USABLE AS AN UNCONVENTIONAL CONSTRUCTION MATERIAL - BOGDAN-VALENTIN PAUNESCU; LUCIAN PAUNESCU; ENIKO VOLCEANOV (Journal of Engineering Studies and Research)
Geopolymer foam with thermal insulation properties was made by foaming the alumino-silicate mixture composed of fly ash and clay brick waste activated with alkaline activator (water glass and sodium hydroxide in aqueous solution). Other mixture components were expanded perlite as siliceous additive, usual fine aggregate (quartz sand), and less frequently used surfactant (olive oil). The main characteristics of the geopolymer foam were: low density, low thermal conductivity, and relatively high compressive strength. The residual materials contributed to low costs and the complete replacement of ordinary cement led to the significant reduction of CO2 emissions.